(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2024)
Substance abuse among adolescents poses a significant challenge to public health and education systems, particularly in developing regions. This study investigates the incidence and impact of substance abuse on secondary school students in Ika South Local Government Area, Delta State, Nigeria. Utilizing a descriptive research approach was employed, the research explores students’ knowledge of drug abuse, its prevalence, and its effects on their academic performance and mental well-being. Data were collected through structured questionnaires distributed to students and interviews with teachers and health officials. Findings indicate that while a majority of students have basic awareness of the dangers of drug abuse, knowledge gaps persist regarding the long-term health and legal implications. Peer pressure, family issues, and socio-economic factors were identified as key drivers of substance use. The study also highlights significant adverse effects on students’ academic performance, including increased absenteeism, declining grades, and behavioral issues. Furthermore, substance abuse was linked to health complications such as anxiety, depression, and risk-taking behaviors. The study underscores the need for comprehensive drug education programs, increased parental supervision, and stronger enforcement of school policies on substance use. It calls for collaboration between schools, community leaders, and healthcare providers to implement targeted interventions aimed at reducing drug abuse and its associated risks. This research contributes to the broader discourse on adolescent health and provides actionable insights for stakeholders in education and public health.